A Mindfulness Workshop for Health Science Graduate Students: Preliminary Evidence for Lasting Impact on Clinical Performance. Issue 2 (June 2019) - Willgens, Annette; Palombaro, Kerstin
Abstract : Introduction: Health science graduate students take high stakes examinations and experience stress and burnout, which can negatively influence performance in clinical courses. The intent of this study was to pilot a curriculum in mindful practice for graduate health science students under high levels of perceived stress. The purpose of this study was to determine the effectiveness of an abbreviated mindfulness workshop to determine if it would provide lasting benefit for students during clinical experiences 9 months later. Methods: Twenty-three graduate students across 4 health professions participated in a 6-week workshop for stress management in March 2017. Students were executed to practice mindfulness activities for 15 minutes daily over the 6 weeks. Weekly meetings included meditation, mindful movement, and small group discussion. A mixed methods approach incorporated pre- and postworkshop measures exploring students' levels of worry, perceived stress, feelings of isolation, self-judgment, self-kindness, overidentification, and mindfulness. Additional survey data were collected 9 months later to determine if the tools learned in the workshop influenced clinical performance. Qualitative comments were coded using generic qualitative analysis, and member checking confirmed themes. Results: Overall, students demonstrated improvements in all measures of stress over the 6-week workshop. Additionally, they reported positive influences on clinical performance in the affective and cognitive domains 9 months later. Four main themes were extracted from the data. These were I Have Tools ; Think, Pause, Allow ; Silence the Critic ; and, I Am Not Alone. Overall, the participants experienced significant improvements in mindfulness scores and self-compassion, and showed improvements in perceived stress and worry (Cognitive-Affective Mindfulness Scale-revised). Discussion and Conclusion: Altogether, these data suggest that (1) graduate students can learn to manage worry, feelings of isolation, and self-judgment using tools and strategies from mindful practices; (2) students who practice mindfulness in a 6-week workshop report lasting effects during clinical performance 9 months later; and (3) students benefit from a community of peers and a shared space to share their thoughts and feelings as emerging health professionals. Suggestions are made for integrating mindful practices into graduate health science education. Abstract : Supplemental Digital Content is Available in the Text.